Peran Liga Arab dalam Upaya Menghentikan Penjajahan Israel di Palestina (2017-2023) - Risanda, Mega Suri (Indonesia Center for Middle East Studies, 2024)
The expulsion and oppression activities carried out by Israel are a major problem that continues to be experienced by the Palestinian people. So it requires attention and support from outside parties, such as the Arab League, to be able to fight for independence for Palestine. In this article, researchers use the theory of organizational roles to analyze the role of the Arab League as an actor, arena and instrument. This research was conducted using a qualitative method from Christopher Lamont. As for the sources and techniques of data collection, they were obtained through archives and documents, both primary, secondary, and those obtained via the internet. The results of this research show that the Arab League continues to demonstrate its role as a regional organization in seeking solutions to stop Israeli colonialism in Palestine, but until now, the Arab League has not succeeded in freeing Palestine from Israel. Due to the inability of member countries to build solidarity and end dependence on the United States, decisions are often made by considering the interests of certain parties.